Post-ERCP Bile Leak - Mathew, Shibi; Zacharias, Prakash; Kumar, Lijesh; Kumar, Arun; Mathews, John; James, Thomas; Ahamed, Hasim; Mohmed, Bilal; Philip, Mathew (Journal of Digestive Endoscopy, 2022)
A 37-year-old female with no underlying comorbidities was referred for the evaluation of biliary stricture. Her magnetic resonance cholangiopancreatography showed a focal lesion in the left hepatic duct close to primary confluence causing a stricture and bilateral intrahepatic biliary radicle dilatation. Spyglass cholangioscopy was done and SpyBite biopsy was taken from the stricture. Repeated attempts at attaining deep cannulation of the right duct were unsuccessful. Patient developed right-sided abdominal pain the next day. Computed tomographic scan of the abdomen showed intra-abdominal fluid in the perihepatic region. Fluid was drained under ultrasound guidance. Though patient improved transiently, she had recurrence of pain after drain removal. A repeat endoscopic retrograde cholangiopancreatography (ERCP) was done and a leak was noted at the junction of right anterior and posterior hepatic ducts. Stenting was done to right anterior, right posterior, and left hepatic ducts. Over the next few days, she improved symptomatically. Though complications are inherent during ERCP, bile duct injury leading to bile leak is rare. Special caution has to be taken in high-risk cases to prevent bile duct injury. Though post-ERCP bile leak is a rare complication, early recognition with a high index of clinical suspicion and prompt management are the key factors in minimizing morbidity and mortality.
Keywords: bile leak; ERCP; spyglass cholangioscopy